Factors affecting consumer attitudes toward the vivo y35 handphone brand - Nugroho, Basuki; Nany, Magdalena (ProBisnis : Jurnal Manajemen, 2024)
Powerful brands have the ability to bypass competitive and crowded markets and can attract and retain their best customers.The aim of this research is to obtain empirical evidence about the influence of brand image, brand trust and advertising exposure on consumer attitudes partially. The research subjects were the community of buyers and users of the Vivo Y35 in Surakarta. The data in this research will be analyzed using multiple regression analysis. The results show that partially brand trust and advertising exposure have significant positive effect on consumer attitudes. While brand image has an insignificant positive effect on consumer attitudes.